Planck Function Distribution in the Far Infrared Cavity Nearby AGB Star at Galactic Latitude 0.6º - Gautam, A. K.; Chhatkuli, D. N. (Journal of Nepal Physical Society, 2020)
A far infrared cavity nearby AGB star namely AGB2308+6058 was found to be located centered at R. A. (J2000)= 23h 06m 54.6s and Dec. (J2000)= 61° 16' 09.8". Distribution of dust color temperature, dust mass and visual extinction of the far infrared cavity have studied. In addition, the distribution of Planck function along the compression and extension of the cavity also has studied. This cavity has found to be located nearby the AGB star around far infrared loop G110+00 at 730 pc. It is close to the Galactic plane at galactic latitude 0.6° therefore the radiation field is strong and the diameter of the cavity is found to be greater than 0.2°. The dust color temperatures was found to be in the range 22.76 ± 0.14 K to 23.55 ± 0.29 K with offset 0.79 K. The contour maps of dust color temperature and dust mass showed that the low temperature region have greater mass density. Planck function showed non-uniform distribution along its extension and compression, suggesting that the dust and grains are not in the local thermodynamic equilibrium, possibly due to nearby AGB star. A clearly noted result is from counter map of dust mass and visual extinction that they showed consistent nature in their distribution.